All Roads Lead to New Rome: The Canonical Origins and Status of the Orthodox and Greek Catholic Churches of Ukraine. (May 2023) - Babie, Paul
Abstract : This article provides a brief account of the historical origins and canonical status of the three modern Orthodox and Greek-Catholic churches of Ukraine: the Orthodox Church of Ukraine, the Ukrainian Orthodox Church-Moscow Patriarchate, and the Ukrainian Greek-Catholic Church. It contains four parts. The first briefly recounts the origins of Byzantine Christianity and the fused form of state and church governance that developed in Constantinople from the 4th to the 15th centuries. The second examines the Great Schism of 1054, which cleaved Eastern and Western Christianity, sending Eastern Orthodox Christianity down the path of territory- or nation-based churches constituted by eucharistic ecclesiology; this would ultimately give rise to the Ukrainian Orthodox Church-Moscow Patriarchate in the Slavic lands that would become Ukraine. The third part considers two modern schisms, the Little Schism of 1596, which produced the Ukrainian Greek-Catholic Church, and the Final Schism of 2018–2019, which brought into existence the Orthodox Church of Ukraine. Drawing upon eucharistic ecclesiology, the final part offers brief concluding reflections concerning the ongoing implications of these three schisms for Orthodox Christianity in Ukraine.